The dialogic life-death in care delivery to adolescents with cancer (Revista Latino-Americana de Enfermagem, 2012)
This study aims to understand the experience of adolescents with cancer, family and the health team regarding death in the healthcare context, in the light of Edgar Morin's proposed theoretical framework of complexity. Participants were 12 adolescents, 14 relatives and 25 health professionals. The interview was used for data collection. The discussion of data was guided by the dialogic life-death in the context of care to adolescents with cancer. It was observed that the singularity in the way the adolescent experiences time and faces death and the possibility that the family will lose a loved one may not be in accordance with the care the health team offers, considering structural, organizational and affective aspects. It is not enough for the team just to rationally make choices on the use of diagnostic-therapeutic devices, in line with predefined moments in the disease. Instead, a contextualized and sensitive understanding of each situation is needed.